ANALISIS FAKTOR-FAKTOR PEMBENTUK KINERJA BANK PADA PERBANKAN INDONESIA (Students' Journal of Accounting and Banking, 2012)
The purpose of this research is to identify the principal components that formed of banking performance and identify of the sequence important principle component forming bank performance based on financial ratios of bank financial statements. The data used are secondary data from published financial statements of banks (2007-2009). The sampling consisted of 49 banking companies registered in the Directorate of Bank Indonesia.Analysis tool used is factor analysis. The important factor in the determination of factor analysis seen from the eigenvalue ≥ 1, and the critical value of the variable rate is determined by loading factor ≥ 0.50. Test the feasibility of the use of factor analysis factor was measured by Bartlett's test -Measure of Sampling Adequacy (MSA) with a criteria KMO’s number (Keiser-Meyer-Oklin) ≥ 0.50 and Index Spherecity X2-Approximate. Then do the grouping variables into the respective component factor of the basic component matrix and rotated component matrix. From this research used 24 variables financial ratios included in the model CAMELS.The test found there are 14 permanent variable to pool the data (overall data). This research concludes that the financial ratios CAMELS model of banking is a form factor banking performance.Keywords: Banking Performance, Financial Ratios, CAMELS, Factor Analysis